Scientific and Social Methods of Interpretation of the Qur’an Alkarim - Abdulhalim Hamid Salih Hamid; M. Imamuddin (PT. Pusmedia Group Indonesia, 2024)
The diversity of methods of interpreting the Qur'an so far shows the intellectual dynamics of Muslims in facing the changing times. The conventional approach that has been developed by classical scholars has begun to be felt to be unable to fully answer increasingly complex and global contemporary problems. The emergence of various new schools of thought, both scientific and social, has enriched and complicated efforts to interpret sacred texts. This raises an urgent need to develop an interpretation method that is able to integrate scientific and social approaches in understanding the meaning and message of the Qur'an. This study aims to explore the possibility of developing a more comprehensive method of interpreting the Qur'an, by combining scientific and social approaches. This study uses a literature study approach to examine the interpretation of the Qur'an. The research method includes collecting detailed library data from primary sources, contemporary interpretation texts, academic journals, and related books. Data analysis is carried out through the partial thematic analysis method, by systematically reviewing the texts to identify scientific topics and concepts that combine modern knowledge with authentic interpretation of the Qur'an. The results of this study show that the general description of the study of the Qur'an and Hadith, and explain the study of the interpretation of the Qur'an and the importance of interpretation in understanding and interpreting the meaning of the Qur'an, understanding objective interpretation and scientific interpretation, and the relationship between scientific interpretation and objective interpretation. This article discusses the advantages and disadvantages of both and also encourages strengthening cooperation between experts in various disciplines to understand the interpretation of the verses of the Qur'an comprehensively and deeply, and also emphasizes the importance of continuous renewal and scientific review in developing our understanding of the Qur'an.